Characteristics of denitrification and anammox in the sediment of an aquaculture pond - Liu, Xingguo; Gao, Meiyun; Wang, Jie; Gu, Zhaojun; Cheng, Guo-feng (Frontiers in Environmental Science, 2022)
Denitrification and anammox are the key processes of nitrogen removal in aquaculture ponds sediment. However, we do not know their nitrogen removal characteristics. In this paper, we set denitrification and an anammox experiment system and supported each the optimal organic carbon, temperature, and nitrate conditions. we found the removal efficiencies of NO2--N, NO3--N, NH4+-N, and TOC in the anammox system were 97.99%, 93.05%, 54.92%, and 58.82%, respectively, but in the denitrification system were 99.82%, 86.10%, 45.74%, and 70.76%, respectively. Comparing the two systems, the removal efficiency of NO2--N and TOC in the denitrification system was higher, whereas the NO3--N and NH4+-N were higher in the anammox system. The Candidatus brocadia is the most important bacteria in nitrogen regu-lation in aquaculture ponds. In general, denitrification has higher nitrogen removal efficiency, but the anammox cannot be ignored.